Enhancing cost estimation performance through effective organizational control: the moderating role of project complexity in construction projects - Mohammad Waffy, Fazil; Puteri Fadzline, Muhamad Tamyez; Lee, Chia Kuang (Taylor & Francis, 2024)
Accurate cost estimation is important for the success of any project, particularly in complex industries like construction. However, many organizations fail to recognize the importance of good cost estimation performance. Previous research has identified various factors that impact cost estimation performance, with most under organizational controls, including input, behaviour, and output controls. Despite this, the causal relationships between these controls and cost estimation performance have not been thoroughly explored, especially from the perspective of diverse project complexities. To address this gap, this paper aimed to evaluate the effect of organizational controls on cost estimation performance, including the moderating effect of project complexity. Data were collected from 152 respondents in Malaysian construction firms, and a Partial Least Squares Structural Equation Modelling (PLS-SEM) method was used for data analysis. This paper reveals that all organizational controls significantly influenced cost estimation performance dimensions, except for one relationship. Additionally, only three moderating effects were found to be significant. These results highlight the importance of effective organizational controls in achieving better cost estimation performance across various levels of project complexity. By implementing the right control modes, organizations can improve their cost estimation performance and enhance project success.